THE EFFECT OF VARIATION OF WELDING CURRENT ON 6061 ALUMINUM PIPE ON MECHANICAL PROPERTIES AND MICRO STRUCTURE USING TIG WELDIN - Aa Santosa; Viktor Noubnome; Maulana Candra Muhkti (Universitas Majalengka, 2023)
Abstract TIG welding is a welding technique for connecting metals using tungsten rod electrodes and using noble gas as a protective gas which is exhaled on the weld metal to protect against contamination with the surrounding atmosphere. Aluminum metal is a metal that has a high affinity for absorbing H2, N2 and O2 in the air at high temperatures, so it is necessary to have a high purity protective gas during the welding process, because N2 H2 and O2 will cause a decrease in the corrosion resistance of the material. To find out the effect of the TIG welding process on the mechanical properties and microstructure, a study was carried out to determine the mechanical properties, namely hardness, and bending properties, as well as the microstructure found in aluminum after the tungsten inert gas welding process was carried out using current. different. In this study the welding process used the Tungsten Innert Gas process by varying the welding current, namely 100 A, 130 A and with a welding time of 2.5 seconds, 4.5 seconds, . So that from the welding parameters used, it will be known the effect of the welding parameters Keywords : Welding Current, Alumnium Metal, TIG welding